Security and Privacy of Internet of Things: A Review of Challenges and Solutions - Lu, Yujing (Journal of Cyber Security and Mobility, 2023)
The Internet of Things (IoT) is a global and comprehensive network that monitors and controls the physical world by collecting, processing, and analysing data derived from IoT devices. Globally, the IoT is emerging as a trend bringing intelligence and automation to a variety of application domains, presenting both opportunities and security challenges. It is used in various fields, including medical care, smart grids, home automation, smart cities, etc. As the number of devices connected to the IoT increases, there is an increased risk of cyber-attacks, data breaches, and other malicious activities. This means that it is essential to have secure protocols and encryption methods in place to protect the data being exchanged. This paper identifies and synthesizes security issues related to the IoT. Security threats across different layers of the IoT architecture are discussed first, followed by identifying prevalent security and privacy issues. A discussion is also provided on security countermeasures.